UJI FITOKIMIA KUALITATIF DAN KUANTITATIF EKSTRAK KULIT BUAH RAMBAI (Baccaurea Motleyana) KONSENTRASI 100% - Diza Afira Hutasuhut; Didit Aspriyanto; I Wayan Arya Krishnawan Firdaus (Dentin, 2022)
ABSRACTBackground: A typical plant from Kalimantan that is effective as a herbal medicine is rambai fruit (Baccaurea Motleyana). The rind of the rambai fruit contains secondary metabolites, namely alkaloids, phenolics, and flavonoids which has activity as an antioxidant, anti-inflammatory, anti-inflammatory, and antimicrobial. Utilization of rambai fruit peel (Baccaurea Motleyana) in addition to the potential to be used as an alternative herbal medicine can also reduce waste from rambai fruit skin. Therefore, quantitative and qualitative phytochemical tests are needed to obtain information on the content of each compound in the rambai fruit peel. Objective: To analyze the results of qualitative and quantitative phytochemical tests of rambai fruit peel extract (Baccaurea Motleyana) with a concentration of 100%. Methods: Non-experimental with qualitative laboratory examination to determine the compound and quantitative to determine the concentration of the sample. Results: The results of qualitative and quantitative phytochemical tests showed that alkaloid compounds were 136.41 mg/ml, saponins were 102.35 mg/ml, phenolic compounds were 109.96 mg/ml, flavonoids were 71.33 mg/ml, triterpenoids were 353, 47 mg/ml, and steroids at 28.71 mg/ml. Conclusion: The highest levels were found in triterpenoids at 353.47 mg/ml and the lowest levels were found in steroid compounds at 28.71 mg/ml.Keywords: Baccaurea Motleyana, Qualitative test, Quantitative test. ABSTRAKLatar Belakang: Tanaman khas dari Kalimantan yang efektif sebagai obat herbal adalah buah rambai (Baccaurea motleyana). Kulit buah rambai memiliki kandungan metabolit sekunder yaitu alkaloid, fenolik, dan flavonoid yang memiliki aktivitas sebagai antioksidan, anti radang, antiinflamasi, dan antimikroba. Pemanfaatan kulit buah rambai (Baccaurea motleyana) selain berpotensi dapat dijadikan alternatif obat herbal dapat juga mengurangi limbah dari kulit buah rambai. Oleh sebab itu, diperlukan uji fitokimia kuantitatif dan kualitatif untuk mendapatkan informasi kandungan tiap senyawa pada kulit buah rambai. Tujuan: Menganalisis hasil uji fitokimia kualitatif dan kuantitatif ekstrak kulit buah rambai (Baccaurea motleyana) konsentrasi 100%. Metode: Non eksperimental dengan pemeriksaan laboratorium secara kualitatif untuk menentukkan senyawa dan kuantitatif untuk menetapkan kadar sampel. Hasil: Hasil uji fitokimia kualitatif dan kuantitatif didapatkan senyawa alkaloid sebesar 136,41 mg/ml, saponin sebesar 102,35 mg/ml, fenolik sebesar 109,96 mg/ml, flavonoid sebesar 71,33 mg/ml, triterpenoid sebesar 353,47 mg/ml, dan steroid sebesar 28,71 mg/ml. Kesimpulan: Kadar tertinggi terdapat pada senyawa triterpenoid sebesar 353,47 mg/ml dan kadar terendah terdapat pada senyawa steroid sebesar 28,71 mg/ml. Kata kunci: Baccaurea Motleyana, Uji Kualitatif, Uji Kuantitatif.